On traditional healing practices: subjectivity and objectivation in contemporary therapeutics (Psicologia USP, 2017)
This article is a theoretical study featuring a brief historical outline of traditional healing practices and also a discussion on their persistence and efficiency in the contemporary world, despite the advances of scientific medicine. Given the increasing relevance of subjectivity in contemporary medicine, our hypothesis aims to emphasize that the objectivation of patients by medical practices eclipses the role of subjectivity and reveals an important deficit in the therapeutics of the biomedical model. Our aim is to understand the role of traditional healing practices and how they may contribute to the medical model.